Error correction approaches and their effects on L2 classroom - Alfaro Castro, Marco Antonio; Calderón Valenzuela, Isbenia Elizabeth; González Mejía, Vilma Elizabeth (2024)
The profession of teaching has become the essential part for the transmission of learning experiences from one generation to another and it helps to develop the right competences to be successful in different professional areas. The learning process should be meaningful for students in order to make it last forever. It is the key for human development in sciences and technologies. For this reason, the main purpose for teachers has to be to encourage students in a positive way to develop their skills by taking into consideration the different error correction techniques used by the teachers. Due to the recent deficiencies seen in the past regarding error correction techniques, this paper seeks to present the reader an overview of the error correction processes and techniques used by teachers at the Foreign Language Department of the University of El Salvador. This document also suggests specific recommendations for the development and improvement of policies and procedures to guarantee a better use of correcting steps so they can result in improvement on the learners´ side. In this way we close an important door for frustration and negative thought that may arise along with learning. Therefore, this will motivate learners to seek an improvement on a daily basis. The present paper includes information regarding the approaches and techniques used in to correct error during learning processes on L2 environments. This also presents a justification that backs up the importance of the topic under study as well as the main objectives of the report.